2020
DOI: 10.7554/elife.60388
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of dynamic pigment cell states at single-cell resolution

Abstract: Cells bearing pigment have diverse roles and are often under strict evolutionary selection. Here, we explore the regulation of pigmented cells in the purple sea urchin Strongylocentrotus purpuratus, an emerging model for diverse pigment function. We took advantage of single cell RNA-seq (scRNAseq) technology and discovered that pigment cells in the embryo segregated into two distinct populations, a mitotic cluster and a post-mitotic cluster. Gcm is essential for expression of several genes important for pigmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 81 publications
(188 reference statements)
4
26
0
Order By: Relevance
“…Overall, this cluster exhibited greatest transcriptional similarity to cell types derived from the ectoderm (Figure 1- Figure supplement 1E), suggesting it may be of ectodermal origin. Consistent with this, a recent study revealed a similar uncharacterized ectodermal cell type (Perillo et al, 2020), further suggesting this cell population exists and is not solely an artifact of our analysis. Taking into account the great plasticity and regeneration capability of the sea urchin larva, it is also possible that this non-differentiated ectodermal cell type is a progenitor population in stasis, waiting to be activated.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, this cluster exhibited greatest transcriptional similarity to cell types derived from the ectoderm (Figure 1- Figure supplement 1E), suggesting it may be of ectodermal origin. Consistent with this, a recent study revealed a similar uncharacterized ectodermal cell type (Perillo et al, 2020), further suggesting this cell population exists and is not solely an artifact of our analysis. Taking into account the great plasticity and regeneration capability of the sea urchin larva, it is also possible that this non-differentiated ectodermal cell type is a progenitor population in stasis, waiting to be activated.…”
Section: Discussionsupporting
confidence: 89%
“…To map known GRN genes, and to identify novel candidates during this critical time period of embryonic development, we performed a scRNA-seq analysis using the 10x Genomics system. This standardized and reproducible advanced scRNA-seq platform yields relatively deep coverage of RNA expression in single cells at a cost that is not prohibitive (Massri et al, 2021; Perillo et al, 2020). Eighteen timepoints were collected, initially at hourly intervals and then during later stages at two to four hour intervals.…”
Section: Resultsmentioning
confidence: 99%
“…Many perturbations of transcription factors and signals from multiple laboratories revealed a detailed network model that operates from fertilization until gastrulation (Davidson et al, 2002; McClay et al, 2020; Peter and Davidson, 2015). Recently, scRNA-seq was used to compile the first atlas of development for Strongylocentrotus purpuratus ( Sp ) (Foster et al, 2020), and that approach was further used to explore the development of pigment cells in Sp (Perillo et al, 2020). Given the extensive knowledge of dGRNs in the sea urchin embryo, and taking advantage of the methods for scRNA-seq developed for this model embryo {Massri, 2021; Perillo et al, 2020), our first goal was to establish whether the molecules in dGRNs were “visible” to scRNA-seq inquiries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal was uniformly distributed during early embryogenesis yet became enriched in mesenchymal cells after the gastrula stage as well as in skeletal rods (Figure 2C, arrows). Not all but some of these DCLK positive cells were also detected by SP1, a pigment cell marker (Figure 2D, arrows) 13,14 . Further, some of the RB1 positive cells were also detected by SP1(Figure 2D, arrows).…”
Section: Resultsmentioning
confidence: 96%